ZAGADNIENIA JĘZYKOZNAWSTWA JAKO TERAPIA W PRZYPADKU PRZEMĘCZENIA - Dovhopolyj, Jarosław (Acta Neophilologica, 2008)
The present article deals with the role which played Marr and Stalin in Soviet linguistics. In the late 1920s and early 1930s, political language came under increasingly strict and unified Party control. The modernist theories of language were replaced by the “new theory developed by Soviet ethnographer and archeologist Nikolai Marr, who argued, in a Marxist evolu- tionist tradition, that language is part of the superstructure and its transformations follow changes in the social base. Linguistic formulations were evaluated by Party experts, among whom Stalin was the chief expert. In 1950 Stalin publicly attacked theoretical schools in Soviet linguistics on the pages of “Pravda” for “vulgar Marxism”. He critiqued Marr’s view of language. He also attacked the view of language as a tool of production, i.e. as a part of the base, the view that was still dominant in the ideological work of the Party organs